2018
DOI: 10.1080/16549716.2017.1413916
|View full text |Cite
|
Sign up to set email alerts
|

From global-to-local: rural mental health in South Africa

Abstract: In this paper, the current situation regarding rural mental health in South Africa is explored. The current status is presented, followed by an attempt to provide approaches and ideas to improve the situation in order to make it more context appropriate and relevant. Issues of staffing, task shifting or sharing, and formal vs informal health care systems are considered and discussed as possible future approaches to improve rural mental health care in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Of the five provinces that received training, two provincial capitals were selected for evaluation: Bloemfontein (Mangaung Metropolitan District, Free State Province), in which 84 healthcare workers received the sensitisation training, and Mafikeng (Ngaka Modiri Molema District Municipality, North-West Province), in which no training intervention was implemented. These locations were selected because they are characteristic of the public health system outside of major South African metropolitan areas (poor infrastructure, under-resourced, operating with inadequate health personnel, and with significant financial and geographic barriers to accessing healthcare), 33,34 and because implementation and scale up of key population HIV programmes in these areas were lacking at the time the research was completed. The number of locations was limited by the resources available for the evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Of the five provinces that received training, two provincial capitals were selected for evaluation: Bloemfontein (Mangaung Metropolitan District, Free State Province), in which 84 healthcare workers received the sensitisation training, and Mafikeng (Ngaka Modiri Molema District Municipality, North-West Province), in which no training intervention was implemented. These locations were selected because they are characteristic of the public health system outside of major South African metropolitan areas (poor infrastructure, under-resourced, operating with inadequate health personnel, and with significant financial and geographic barriers to accessing healthcare), 33,34 and because implementation and scale up of key population HIV programmes in these areas were lacking at the time the research was completed. The number of locations was limited by the resources available for the evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, most participants in the study described shortages of staff as a significant challenge within the facilities where they access their treatment, despite the treatment they receive. This is supported by a study by Vergunst 26 who suggested that rural areas in South Africa often do not have psychiatrists or psychologists and rely primarily on general practitioners (GPs) and nurses for mental health interventions. This has been highlighted further by a study by the SAHRC 6 which indicated that in 2017 the South African Society of Psychiatry reported that there were only six psychiatrists working in the entire public mental health system in the Limpopo province and facilities such as Hayani specialist mental health hospital did not have a psychiatrist on staff.…”
Section: Resultsmentioning
confidence: 92%
“…A study by Vergunst 26 indicated that rural communities in South Africa experience significant barriers to accessing healthcare. It is important to consider this relatively recent research publication at this juncture, as it demonstrates about the current the challenges of persons living with mental disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined communication technology interventions often result in effective health outcomes and are feasible substitutes for traditional health promotion approaches such as printed material [ 52 , 53 ]. Vergunst [ 54 ] also recommended that creative interventions need to be established for caregivers in resource-poor settings such as rural areas to bridge gaps in mental health service delivery for the individual, the family, and the community. Although communication technology interventions are potentially valuable to support caregivers of children with mental and behavioral problems [ 55 ], limited data are available even though it is a major public health concern [ 56 ].…”
Section: Introductionmentioning
confidence: 99%